PENGENALAN HTML: FONDASI MEMBUAT WEBSITE UNTUK SISWA SMA DI SMA GITA KIRTTI 3 JAKARTA SELATAN - Aulivia Zulianti Majid; Dafa Alfiansyah; Dwi Prasetyo Nugroho; Farissa Nadya; Fariz Afdilah Muhamad; Muhamad Febryansyah; Muhammad Reza; Nabila Indah Kurniadi; Sheva Ardiansyah; Nurhasanah (Abdi Jurnal Publikasi, 2025)
This Community Service (PKM) activity aims to introduce the basics of website development using HTML to students of SMA Gita Kirtti 3 South Jakarta. The lack of students' understanding of the basic structure of web pages is the background to this activity. Through a learning by doing approach, training is carried out in the form of direct practice in creating HTML-based profile pages. The evaluation results show an increase in students' interest and understanding of basic web technology. This activity is expected to be an initial foundation for improving digital literacy in high school environments.